2020
DOI: 10.1016/j.heliyon.2020.e04507
|View full text |Cite
|
Sign up to set email alerts
|

Kratom instrumentalization for severe pain self-treatment resulting in addiction – A case report of acute and chronic subjective effects

Abstract: Background Kratom is a Southeast Asian plant, which is widely used in this region, and making an increasing appearance in Europe and the US. Case report We present the case of a 26-year-old man in Substitol-assisted treatment of excessive Kratom and Tilidin use expressing the wish for a drug-free management of a chronic pain condition. After an accidental calcaneus impression fracture, the patient was suffering from severe chronic pain and anxiety of further accidents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
(51 reference statements)
1
23
0
5
Order By: Relevance
“…The latter case and four other cases of kratom withdrawal were treated successfully with buprenorphine-naloxone maintenance ( 98 100 ). A further withdrawal from combined kratom-tilidine addiction has been successfully treated with retarded morphine ( 101 ). Finally, a recent paper reported an unusual presentation of obsessive-compulsive disorder-like syndrome during kratom withdrawal that responded to lorazepam ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter case and four other cases of kratom withdrawal were treated successfully with buprenorphine-naloxone maintenance ( 98 100 ). A further withdrawal from combined kratom-tilidine addiction has been successfully treated with retarded morphine ( 101 ). Finally, a recent paper reported an unusual presentation of obsessive-compulsive disorder-like syndrome during kratom withdrawal that responded to lorazepam ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…An important question that arises from the current case is the potential sudden loss of efficacy of Kratom in self-management of major depression and generalized anxiety disorder. The loss of functionality may have its origin in non-pharmacological factors ( Ahmed et al., 2020 ) as well as in non-Kratom related pharmacological factors ( Müller et al., 2020 ). The patient reported a massive increase in stress level short before long-term effective Kratom started to fail.…”
Section: Discussionmentioning
confidence: 99%
“…A particular risk of any Kratom instrumentalization is the establishment of a Kratom addiction and emerging cognitive deficits, as it was shown for Kratom and its main psychoactive alkaloids ( Yusoff et al., 2016 ; Ismail et al., 2017 ; Hassan et al., 2019 ; Swogger and Walsh, 2018 ). Other case studies have also brought up cases of problematic Kratom use in Europe and the U.S., in particular in the self-management of severe pain ( Müller et al., 2020 ; Metastasio et al., 2020 ) or in the context of opiate ( Boyer et al., 2007 ; Singh et al., 2020 ) or alcohol self-withdrawal ( Havemann-Reinecke, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases have been reported in both Western (53-55), including cases of neonatal abstinence syndrome (56,57), and Eastern countries (27,58,59), where those who used kratom for a long time experienced both physical (e.g., constipation) and psychological (e.g., anxiety) withdrawal symptoms. More recently an article have been published by Muller et al (60) in which an individual self-prescribing kratom for pain treatment reported an escalation of the dosage needed and eventually developed a dependence.…”
mentioning
confidence: 99%